Energy Conservation In a Room Using Sensors - Rajesh Kr. Yadav, Shanya Verma, Prishita Singh (International Journal of Advanced Science and Technology, 2020)
Increasing demand and cost of the energy has driven many organizations to find various smart ways for monitoring, controlling and preserving the energy. The ever rising technology of the Internet of Things (IoT) [6]- [7] can be most efficient to manage the energy utilization in different sectors. Many devices can help in making the various interactions in between the people and their house duties easy. This paper proposes use of various types of sensors to perform temperature regulation of the room.  Major problem with the conventional techniques for minimizing the energy consumption of the air conditioners is the inability of the systems to accurately predict the occupancy of the room. However, various other factors as well have been considered, both external and internal like the energy dissipated by sunlight, electricity humidity etc. In the end, a function of these parameters is made in order to predict the temperature of the room. Usage of IoT are widening quickly. This project has expanding scope as it can be used in various places such as party halls and can help in conservation of energy.Keywords–Energy Efficiency, Temperature Regulation, motion sensor, temperature and humidity sensor, IoT